Enhancing γ-Aminobutyric Acid (GABA) in Boza, a Fermented Turkish Beverage: Role of Monosodium Glutamate and Lactobacillus Strains - Alkay, Zuhal; Tuncil, Yunus Emre; Durak, Muhammed Zeki; Yilmaz, Mustafa Tahsin; Dertli, Enes (WILEY, 2025)
Research Background: Enrichment of fermented foods with gamma-aminobutyric acid (GABA) is one of the recent strategies to obtain novel functional foods, and this fermentation process is led by GABA producer suitable lactic acid bacteria strains. Adaptation of high GABA-producing LAB strains to the fermentation environments is key, and boza, a cereal-based fermented beverage, might be a suitable environment to obtain physiologically relevant levels of GABA.Experimental Approach: The objective of this study is to investigate the effect of monosodium glutamate (MSG)-induced in situ production of GABA on physicochemical, microbiological, viscoelastic, and sensory characteristics of boza at different fermentation (0, 24, 48, and 72 h) and storage (1, 3, 6, and 9 days) times, utilizing GABA-producing sourdough isolates: Lactiplantibacillus plantarum SD30 and Levilactobacillus brevis SD48 strains.Results and Conclusions: Boza samples supplemented with MSG showed higher counts of lactic acid bacteria. MSG addition significantly induced GABA production in boza; moreover, the addition of MSG to boza, combined with fermentation by L. plantarum SD30, yielded the maximum amount of GABA, reaching 0.13 mg/mL. The MSG-induced production of GABA in boza significantly increased both elastic (G ') and viscous (G '') properties. Glucose and fructose amounts were lower in samples added with MSG, suggesting that MSG addition might have utilized glucose and fructose by the strains. Boza samples added with MSG received higher scores, which could be attributed to the impact of MSG on taste perception in boza.Novelty and Scientific Contribution: This study highlights the potential of MSG-induced in situ GABA production by two LAB strains as starter cultures for the production of boza with improved viscoelastic and sensory properties.
Keywords: gamma-aminobutyric acid (GABA); boza; functional and viscoelastic properties; lactic acid bacteria (LAB) strains; monosodium glutamate (MSG); PHYSICOCHEMICAL CHARACTERISTICS; SENSORY PROPERTIES; CEREAL BEVERAGE; BIOGENIC-AMINES; BACTERIA; SOURDOUGH; SYSTEM; BREVIS; HEAT; Food Science & Technology